Effects of a Portable Peritoneal Lavage Device on Dogs with Seawater-Immersed Open Abdominal Injury - Song Zhou; Kai Nie; Wenhua Zhang; Zhihong Shao; Wei Zhong; Qinglin Ye; Xiaoqiang Lin; Yuefeng Chen; Xiaowen Wang (Gastroenterology Research and Practice)
Background. Seawater-immersed open abdominal injury is a special injury during marine activities. Effective warmed peritoneal lavage in the field early after injury is the key to treatment. This pilot study aimed at exploring the treatment effects of a self-developed portable peritoneal lavage device compared with conventional treatment model. Material and Methods. Beagle dogs were used to develop models of seawater-immersed open abdominal injury. A conventional lavage method or a novel peritoneal lavage device was used for lavage and rewarming. The vital signs, electrolyte, serum inflammatory cytokine expression levels, histological changes of mucosa, and microstructure variety of different groups were observed and compared before and after immersion and 2 h, 1 d, 3 d, and 5 d after lavage. Results. The levels of TNF-α, IL-1β, IL-8, IFN-γ, VEGF, and TGF-β in the blood and the damage of tissues and cells in three groups were increased after immersion and decreased at the later points of time after lavage. The concentration of Na+, K+, Cl-, lactate, and lactate dehydrogenase in the plasma was significantly higher than that before immersion (P<0.05), and the concentration of Ca2+ and HCO3- and plasma pH decreased slightly (P<0.05). The degree of tissue inflammation and mucosal injury in the delayed control group and device group was lower than the control group. Conclusions. Timely lavage and rewarming using a portable peritoneal lavage device reduced the inflammatory response of seawater-immersed open abdominal injury dogs and reduced the damage of multiple organs. The dogs recovered better and faster than the conventional treatment group.